Peruvian agro-exports' competitiveness: An assessment of the export development of its main products - Jose Carlos Montes Ninaquispe; Alberto Luis Pantaleón Santa María; Diego Alejandro Lude\~na Jugo; William Teófilo Castro Mu\~noz; Juan Cesar Farias Rodriguez; Billy Heinrich Maco Elera; Kelly Cristina Vasquez Huatay (Economies, 2024)
This study analyzed the competitiveness of Peru's exports of grapes, blueberries, avocados, and asparagus from 2019 to 2023. Data were obtained from the customs declarations of all exporting companies of the analyzed products, along with data from the International Trade Center. Competitiveness was measured using the absolute revealed comparative advantage (RCA) index. The results indicate notable growth in the exports of grapes and blueberries, while asparagus and avocados face challenges in market and exporter diversification. The RCA index suggests a strong and stable specialization in these products. This study concludes with specific recommendations for institutions such as Ministerio de Desarrollo Agrario y Riego (MIDAGRI), Comisión de Promoción del Perú para la Exportación y el Turismo (PROMPERÚ), Asociación de Exportadores (ADEX), and Instituto Nacional de Innovación Agraria (INIA), aimed at enhancing competitiveness through market diversification.
Keywords: 330; agro-exports; export development; international competitiveness; Peru; RCA